(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objectives: To understand how caregivers of people with malignant neoplastic wounds perform care at home. Method: A qualitative study that involved seven relatives of people with malignant wounds undergoing treatment in a high complexity oncology unit. The data were produced through semistructured interviews and submitted to thematic content analysis, proposed by Bardin. Results: Seven family-caregivers, all female, young people who left work to dedicate themselves to the sick person were interviewed. Three categories emerged after content analysis: family members seek guidance to care for patients with malignant neoplastic wounds at home; they adopt strategies in wound care; and report the need for support from health professionals and institutions, because they face difficulties in care, especially in primary care units. Conclusion: Family members of people with malignant neoplastic wounds face difficulties, mainly due to the scarcity of technical knowledge and lack of support from health institutions and from professionals.